2015
DOI: 10.1371/journal.pntd.0003850
|View full text |Cite
|
Sign up to set email alerts
|

BoHV-4-Based Vector Single Heterologous Antigen Delivery Protects STAT1(-/-) Mice from Monkeypoxvirus Lethal Challenge

Abstract: Monkeypox virus (MPXV) is the etiological agent of human (MPX). It is an emerging orthopoxvirus zoonosis in the tropical rain forest of Africa and is endemic in the Congo-basin and sporadic in West Africa; it remains a tropical neglected disease of persons in impoverished rural areas. Interaction of the human population with wildlife increases human infection with MPX virus (MPXV), and infection from human to human is possible. Smallpox vaccination provides good cross-protection against MPX; however, the vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 80 publications
0
34
0
Order By: Relevance
“…Despite the absence of type I and II interferon function, STAT129 mice were shown to develop strong adaptive immune responses to virus infections (Vancott et al 2003, Franceschi et al 2015 or vaccination with experimental subunit vaccines (Vancott et al 2003, Raymond et al 2011. Although this suggests that the model is suitable for the evaluation of candidate vaccines, the high susceptibility of STAT129 mice to virus infection may result in undervaluing the vaccine potential of experimental vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the absence of type I and II interferon function, STAT129 mice were shown to develop strong adaptive immune responses to virus infections (Vancott et al 2003, Franceschi et al 2015 or vaccination with experimental subunit vaccines (Vancott et al 2003, Raymond et al 2011. Although this suggests that the model is suitable for the evaluation of candidate vaccines, the high susceptibility of STAT129 mice to virus infection may result in undervaluing the vaccine potential of experimental vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…However, BoHV-4-mxCT-transduced cells expressed mxCT, as revealed by western blotting ( Figure 1E). A virus expressing the unrelated A29 Monkeypoxvirus glycoprotein (BoHV-4-A29) 38 was used as a control.…”
Section: Generation Of a Recombinant Virus That Delivers Mxct Expressmentioning
confidence: 99%
“…The Zaire Ebola virus Mayinga strain glycoprotein (GP) sequence, identical to the Gabon-94 strain and highly conserved with the new isolates (accession number: KJ660346.2, KJ660347, KJ660348), was used as a template to obtain its nucleotide sequence by reverse translation, which was human codon usage adapted and tagged at the carboxy-terminal with gD106 tag peptide [10, 20] (Fig. 1a, b).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies, which demonstrated the ability of BoHV-4 based vectors to efficiently protect against the Category A agent Monkeypox virus [10], it can be assumed that the use of BoHV-4 vector based platform represents an effective tool to test unknown antigens and vectors for class A pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation